Kolaborasi Digital Signage dan Chatbot Messenger Sebagai Layanan Penyedia Informasi Akademik - Jumardi, Rio; Farokhah, Lia; Maghfirah, Maghfirah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
At present, the dissemination of information is easier to obtain and spread in various forms of print and electronic, but sometimes it is still presented with poor quality. The high quality of  information makes that information be transformed into knowledge that is the basis for decision making and become a separate power source for the agency or organization. The use of technology to share knowledge an organization is necessary as a means of improving the effectiveness of the technology and business processes. System development methodology used in this research using GRAPPLE which stands for Rapid Application Guidelines for Requirements Engineering with the stage of Gathering, Analysis, Design, Development and Deployment. Digital boards based on digital or digital signage can replace information boards made from conventional materials such as wood or iron by providing accurate, relevant, timely and dynamically working information. Chatbot messenger can help provide academic information to students in two directions with the concept of request-response from and to students via telegram messenger.Collaboration between digital signage and chatbot messenger can help students in fulfilling academic related information effectively and efficiently